Alteration of Wax Ester Content and Composition in Euglena gracilis with Gene Silencing of 3‐ketoacyl‐CoA Thiolase Isozymes. Issue 5 (10th April 2015) - Nakazawa, Masami; Andoh, Hiroko; Koyama, Keiichiro; Watanabe, Yomi; Nakai, Takeo; Ueda, Mitsuhiro; Sakamoto, Tatsuji; Inui, Hiroshi; Nakano, Yoshihisa; Miyatake, Kazutaka
Abstract: Euglena gracilis produces wax ester under hypoxic and anaerobic culture conditions with a net synthesis of ATP. In wax ester fermentation, fatty acids are synthesized by reversing beta‐oxidation in mitochondria. A major species of wax ester produced by E. gracilis is myristyl myristate (14:0‐14:0Alc). Because of its shorter carbon chain length with saturated compounds, biodiesel produced from E. gracilis wax ester may have good cold flow properties with high oxidative stability. We reasoned that a slight metabolic modification would enable E. gracilis to produce a biofuel of ideal composition. In order to produce wax ester with shorter acyl chain length, we focused on isozymes of the enzyme 3‐ketoacyl‐CoA thiolase (KAT), a condensing enzyme of the mitochondrial fatty acid synthesis pathway in E. gracilis . We performed a gene silencing study of KAT isozymes in E. gracilis . Six KAT isozymes were identified in the E. gracilis EST database, and silencing any three of them (EgKAT1‐3) altered the wax ester amount and composition. In particular, silencing EgKAT1 induced a significant compositional shift to shorter carbon chain lengths in wax ester. A model fuel mixture inferred from the composition of wax ester in EgKAT1‐silenced cells showed a significant decrease in melting point compared to that of the control cells.